Imaging correlates of pathology in corticobasal syndrome [Image: see text] - Whitwell, J.L. (American Academy of Neurology, 2010)
BACKGROUND: Corticobasal syndrome (CBS) can be associated with different underlying pathologies that are difficult to predict based on clinical presentation. The aim of this study was to determine whether patterns of atrophy on imaging could be useful to help predict underlying pathology in CBS. METHODS: This was a case-control study of 24 patients with CBS who had undergone MRI during life and came to autopsy. Pathologic diagnoses included frontotemporal lobar degeneration (FTLD) with TDP-43 immunoreactivity in 5 (CBS-TDP), Alzheimer disease (AD) in 6 (CBS-AD), corticobasal degeneration in 7 (CBS-CBD), and progressive supranuclear palsy in 6 (CBS-PSP). Voxel-based morphometry and atlas-based parcellation were used to assess atrophy across the CBS groups and compared to 24 age- and gender-matched controls. RESULTS: All CBS pathologic groups showed gray matter loss in premotor cortices, supplemental motor area, and insula on imaging. However, CBS-TDP and CBS-AD showed more widespread patterns of loss, with frontotemporal loss observed in CBS-TDP and temporoparietal loss observed in CBS-AD. CBS-TDP showed significantly greater loss in prefrontal cortex than the other groups, whereas CBS-AD showed significantly greater loss in parietal lobe than the other groups. The focus of loss was similar in CBS-CBD and CBS-PSP, although more severe in CBS-CBD. CONCLUSIONS: Imaging patterns of atrophy in CBS vary according to pathologic diagnosis. Widespread atrophy points toward a pathologic diagnosis of FTLD-TDP or AD, with frontotemporal loss suggesting FTLD-TDP and temporoparietal loss suggesting AD. On the contrary, more focal atrophy predominantly involving the premotor and supplemental motor area suggests CBD or PSP pathology. GLOSSARY: AAL: = automated anatomic labeling; AD: = Alzheimer disease; CBD: = corticobasal degeneration; CBS: = corticobasal syndrome; CDR-SB: = Clinical Dementia Rating sum of boxes; FDR: = false discovery rate; FTLD: = frontotemporal lobar degeneration; MMSE: = Mini-Mental State Examination; PSP: = progressive supranuclear palsy; ROI: = region of interest; SMA: = supplemental motor area; TDP: = TDP-43 immunoreactivity; TIV: = total intracranial volume; VBM: = voxel-based morphometry.